Improving a resourcesaving surfacing technology using two ribbon electrodes with a controlled transfer of electrode's metal - Lavrova, Elena; Ivanov, Vitaliy; Royanov, Vyacheslav; Zakharova, Irina; Kibish, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2019)
This paper reports results of research into a resource-saving technology of surfacing with two ribbon electrodes with a controlled transfer of the electrode's metal from the end sides of ribbon electrodes and with an adjustable ratio between the ribbon electrodes' feed speed. To implement the proposed technology of surfacing, we designed a device that makes it possible to change the ratio between feed speeds of the first and second electrodes in a wide range. That provides for a controlled heat-mass transfer to the welding bath. As well as, accordingly, a controlled fusion of ribbon electrodes and the distribution of thermal energy throughout a welding bath. This makes it possible to improve quality of the surfaced products using a simple and reliable resource-saving device. A given design makes it possible to optimize parameters for a pulsed mechanical transfer and prevent the deformation of ribbon electrodes, to ensure an alternating reciprocation motion of the ribbon electrodes' end sides at optimal frequency and amplitude. That provides for the optimal size of the surfaced bead while making it possible to reduce the consumption of an electrode's metal for loss and overheating, and, accordingly, the consumption of energy for melting, as well as ensure a resource saving technology of surfacing. The process of surfacing with two electrodes, even when using fluxes recommended for arc welding, occurs partially similar to the electroslag process, because a certain percentage of current is shunted by the molten slag. This helps reduce the depth of welding and lowers the share of the base metal in the surfaced metal. The main advantage of surfacing with two ribbon electrodes is obtaining the surfaced metal with the required chemical composition as early as in the first or second layer, in contrast to the single-electrode surfacing where it is necessary to apply from 3 to 5 layers. Results of research into the influence of oscillation frequency of ribbon electrodes have revealed that the maximum increase in a melting coefficient occurs at oscillation frequency in the range of 45‒55 Hz regardless of other mode parameters